2013
DOI: 10.1155/2013/610373
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Role of HPV Testing in Primary and Secondary Cervical Cancer Screening

Abstract: Traditional population-based cervical screening programs, based on cytology, have successfully reduced the burden of cervical cancer. Nevertheless limitations remain and new screening methods are emerging. Despite vaccination against the 2 most oncogenic types (HPV 16/18), cervical cancer screening will have to continue as an essential public health strategy. As the acquisition of an HR-HPV infection is critical in the progression to (pre-)cancerous cervical lesions, recent research has focused on HR-HPV detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Knowledge of the proportion of the cancers that can be prevented by reducing the prevalence of HPV infections provides a critical baseline for evaluating the effectiveness of interventions and contribute to analyses of the added value of such interventions [16]. HPV vaccinations, for example, will substantially reduce the burden of HPV associated diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the proportion of the cancers that can be prevented by reducing the prevalence of HPV infections provides a critical baseline for evaluating the effectiveness of interventions and contribute to analyses of the added value of such interventions [16]. HPV vaccinations, for example, will substantially reduce the burden of HPV associated diseases [17].…”
Section: Introductionmentioning
confidence: 99%
“…Information on country-specific HPV genotype prevalence is needed to inform local policy, screening and prevention programmes. Randomised trials have demonstrated that HPV-based screening is more effective than cytological screening in reducing the incidence of invasive squamous and adeno-carcinoma of the cervix uteri [18, 19]. The current prevalence of HPV infection in Swaziland remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…When HPV acquisition is followed by HPV persistence instead of clearance, there is a high chance for progression to precancerous lesions and ultimately invasive lesions. HPV is a double stranded closed circular DNA virus with the capacity to incorporate in the human DNA (Hoste et al, 2013). HPV infection is the most common sexual transmitted disease with more than 80% of the population infected at some time in their life.…”
Section: Discussionmentioning
confidence: 99%